The Influence of Promotion and Price on Product Purchasing Decisions at XL Center Pekanbaru - Pertiwi, Vira; Aritonang, Esrawati (First Ciera Publisher, 2024)
The purpose of this study was to determine the effect of promotion and price on purchasing decisions at XL Center Pekanbaru. The sample in this study was 100 consumers. Data analysis used was validity test, reliability test, classical assumption test, multiple linear regression, hypothesis test and determination coefficient test. Based on the results of the study, it is known that through partial test (t-test) there is a significant effect of promotion on purchasing decisions with the test results known t count (2.377) > t table (1.984) and Sig. (0.000) < 0.05. There is a significant effect of price on purchasing decisions with the test results known t count (11.096) > t table (1.984) and Sig. (0.000) < 0.05. Simultaneously shows that Promotion (X1) and Price (X2) together influence Purchasing Decisions at XL Center Pekanbaru with the test results known Fcount (76,678) > Ftable (3.09) with a significance of 0.000 < 0.05. In terms of determination coefficient, the promotion and price variables have an influence of 61.3% on purchasing decisions while the remaining 38.7% is explained by other factors not studied by the author.